Students’ attitude toward personal attitude factors, financial knowledge factors and practices of credit card factors: a study in UiTM Kampus Bandaraya Melaka / Muhammad Edham Nasir and Amylia Ayut Santok - Nasir, Muhammad Edham; Santok, Amylia Ayut (Faculty of Business and Management, 2013)
students are the most targeting viable target audiences especially the college-age generation y consumer cohort to credit cards has been a challenging research agenda for many years (see e.g. blair, 1997; chen and volpe, 1998; noble et al., 2009). based on the research of braunsberger et al., 2004; commercial law bulletin, 1997 indicates that the majority of college students with percentage 75 per cent tend to hold on to their first credit card brand for an average of fifteen years old. Based on the research done on overseas country, united stated, we would like to conduct the same research in UiTM Kampus Bandaraya Melaka and to measure the used of credit card by local student in Melaka. The purpose of this research is to investigate the relationship that may exist between students’ attitudes toward credit card as dependent variables and for independent variables which consist of personal attitude factor, personal financial knowledge factor, and credit card factors. The relationship between dependent variables and independent variables maybe positively or negatively related. The researcher collects the information using cluster samples. This study is based on a questionnaire survey conducted in UiTM Kampus Bandaraya Melaka students. 50 questionnaires were distributed and we managed to get back all the questionnaires. The purpose of this study is to investigate whether there is positive or negative relationship between dependent variables and independent variables, Pearson correlation analysis was used to determine the relationship between the variables. The findings of this study can be useful information to credit card holder especially for students to use their credit card in effective way and make useful all the advantage of credit card. Through this study, there are several useful recommendation have been provide to improve and given new knowledge that can help to manage the increasing percentage of bankruptcy among students.